Inactivation of Pseudomonas aeruginosa Biofilms by 405-Nanometer-Light-Emitting Diode Illumination - Yang, Yanpeng (Appl Environ Microbiol, 2020)
Biofilm formation by Pseudomonas aeruginosa contributes to its survival on surfaces and represents a major clinical threat because of the increased tolerance of biofilms to disinfecting agents. This study aimed to investigate the efficacy of 405-nm light-emitting diode (LED) illumination in eliminating P. aeruginosa biofilms formed on stainless steel coupons under different temperatures. Time-dependent killing assays using planktonic and biofilm cells were used to determine the antimicrobial and antibiofilm activities of LED illumination. We also evaluated the effects of LED illumination on the disinfectant susceptibility, biofilm structure, extracellular polymeric substance (EPS) structure and composition, and biofilm-related gene expression of P. aeruginosa biofilm cells. Results showed that the abundance of planktonic P. aeruginosa cells was reduced by 0.88, 0.53, and 0.85 log CFU/ml following LED treatment for 2 h compared with untreated controls at 4, 10, and 25°C, respectively. For cells in biofilms, significant reductions (1.73, 1.59, and 1.68 log CFU/cm(2)) were observed following LED illumination for 2 h at 4, 10, and 25°C, respectively. Moreover, illuminated P. aeruginosa biofilm cells were more sensitive to benzalkonium chloride or chlorhexidine than untreated cells. Scanning electron microscopy and confocal laser scanning microscopic observation indicated that both the biofilm structure and EPS structure were disrupted by LED illumination. Further, reverse transcription-quantitative PCR revealed that LED illumination downregulated the transcription of several genes associated with biofilm formation. These findings suggest that LED illumination has the potential to be developed as an alternative method for prevention and control of P. aeruginosa biofilm contamination. IMPORTANCE Pseudomonas aeruginosa can form biofilms on medical implants, industrial equipment, and domestic surfaces, contributing to high morbidity and mortality rates. This study examined the antibiofilm activity of 405-nm light-emitting diode (LED) illumination against mature biofilms formed on stainless steel coupons. We found that the disinfectant susceptibility, biofilm structure, and extracellular polymeric substance structure and composition were disrupted by LED illumination. We then investigated the transcription of several critical P. aeruginosa biofilm-related genes and analyzed the effect of illumination temperature on the above characteristics. Our results confirmed that LED illumination could be developed into an effective and safe method to counter P. aeruginosa biofilm contamination. Further research will be focused on the efficacy and application of LED illumination for elimination of complicated biofilms in the environment.